The Impact of ICT on Women Empowerment: Evidence from Selected South Asian Countries - Muhammad Hafeez; Zubaria Andlib; Ayesha Naz; Sana Ullah (NUST Journal of Social Sciences and Humanities, 2021)
During the current epoch, information and communication technology (ICT) is considered as one of the core drivers towards women empowerment. The principal concern of the underlying study is to evaluate dynamic linkage among ICT, women empowerment, fertility rate, labour force and trade openness for selected South Asian countries from 2000 to 2016 by mean-group and pooled mean-group estimators that are robust to endogeneity and heterogeneity. The outcomes infer that ICT enhances women empowerment in South Asian countries. However, fertility rate negatively contributes to women empowerment. Sensitivity analysis using fully modified ordinary least square (FMOLS) method is applied to check the validation, consistency, and robustness of the study for future policy implications. The analytics surmise future strategy for women empowerment with confined ICT expansion and discouraging fertility in South Asian countries.